2015
DOI: 10.1111/wrr.12340
|View full text |Cite
|
Sign up to set email alerts
|

Microclimate is an independent risk factor for the development of intraoperatively acquired pressure ulcers in the park‐bench position: A prospective observational study

Abstract: Preventing pressure ulcers is important in patients undergoing procedures in the park-bench position. We hypothesized that the microclimate around the skin is a significant risk factor for developing pressure ulcers. This research continuously assessed factors of the microclimate in terms of skin temperature and perspiration as well as the interface pressure in order to determine whether the microclimate is an independent risk factor for the development of park-bench position-related pressure ulcers (PBP-PUs).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
2
5

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(43 citation statements)
references
References 27 publications
0
36
2
5
Order By: Relevance
“…45,46 Sweat and climate affect the skin microclimate, which affects skin vulnerability to pressure ulcers from friction and shearing. 47,48 In our patient cohort, we found that gender had no significant association with many of the expected risk variables, such as BMI, ASA grade, pre-op Braden score, and age. However, a recent nationwide survey in Singapore reported that older Singaporean females were more malnourished and frail compared with their male counterparts.…”
Section: Resultsmentioning
confidence: 69%
See 1 more Smart Citation
“…45,46 Sweat and climate affect the skin microclimate, which affects skin vulnerability to pressure ulcers from friction and shearing. 47,48 In our patient cohort, we found that gender had no significant association with many of the expected risk variables, such as BMI, ASA grade, pre-op Braden score, and age. However, a recent nationwide survey in Singapore reported that older Singaporean females were more malnourished and frail compared with their male counterparts.…”
Section: Resultsmentioning
confidence: 69%
“…A humid environment delays evaporation of sweat, but residents of tropical areas sweat less and more slowly than residents of temperate areas . Sweat and climate affect the skin microclimate, which affects skin vulnerability to pressure ulcers from friction and shearing …”
Section: Discussionmentioning
confidence: 99%
“…However, there was no statistically significant relation between skin oedema condition and the occurrence of blanchable erythema, which might be associated with the rapid development of pressure injuries in patients with skin oedema. Yoshimura et al () pointed out that intraoperative temperature was an independent risk factor for intraoperative pressure injuries. Patients with higher body temperature of above 38.1°C were more likely to develop intraoperative pressure injuries.…”
Section: Discussionmentioning
confidence: 99%
“…We previously reported that hyperthermia was an independent risk factor for the development of IAPUs in neurosurgery performed in the park‐bench position . There has also been recent discussion that microclimate control may play a key role in preventing pressure ulcers .…”
Section: Discussionmentioning
confidence: 99%